THE ARTERIOVENOUS HEMANGIOMA OF THE RIGHT VENTRICLE: CASE REPORT AND LITERATURE REVIEW - Mikic, Aleksandar; Matkovic, Milos; Vukicevic, Petar; Obrenovic Kircanski, Biljana; Karamarkovic, Nemanja; Velinovic, Milos; Samanovic, Marko; Putnik, Svetozar (Vojnosanitetski pregled, 2021)
Introduction: Cardiac hemangiomas of the right ventricle are very rare and mostly asymptomatic benign tumors. The surgical excision is the first line treatment. Case report: We report a case of 69-year old woman with an asymptomatic arteriovenous hemangioma of the right ventricle. Compete surgical excision was performed with the use of cardiopulmonary bypass and the patient was discharged on postoperative day 6 with no relapse at the six months follow-up. Conclusion: The review of the literature showed that this procedure can be performed safely with excellent long term results. Keywords: cardiac hemangioma, right ventricle, surgery